A study on the assessing the role of employees’ engagement on employees’ productivity at Bank Simpanan Nasional (BSN) Negeri Sembilan / Nur Syarafina Noor Azland - Noor Azland, Nur Syarafina (Faculty of Business and Management, 2014)
Employees play the important role towards the organization. The organization cannot achieve their goals without the productivity from the employees. This paper aims to study on assessing the role of employee engagement on employees’ productivity at Bank Simpanan Nasional (BSN) Negeri Sembilan. The independent variables includes in this study are job characteristic, perceived organizational support and reward and recognition. For this project, the research focused on the employee who works at Bank Simpanan Nasional (BSN) Negeri Sembilan. 158 of questionnaires were gathered in this research. The questionnaires were used to obtain and collected the data from the respondent. Stratified random samplings are being used in this study as sampling method. The researcher have used SPSS program version 20.0 where the researcher have used reliability analysis, frequency analysis, correlation and multiple regression analysis. In the last part of this paper, several recommendations have being provided to increase the productivity among employees’.